PERCEIIVED SOCIAL HEALTH NEEDS FOR ACHIEVEMENT OF OPTIMAL HEALTH AMONG VULNERABLE CHILDREN IN BENIN CITY, EDO STATE - OBASUYI , Osato; IGUDIA , Enoma; IDEHEN, Prof Cosmos (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This study was aimed at examining the perceptions of vulnerable children with respect to the social health needs necessary for achieving their optimal health. The descriptive survey research method was adopted and sixty six vulnerable children were randomly selected to respond to the variables of social health needs such as love and belonging needs, esteem needs and self-actualization needs. The sampled respondents responded to a 21-item researcher-made questionnaire. Three research questions were raised and frequency counts and percentages were used to provide answers to them. with a bench mark of 50% and above or below in three centres for acceptance and rejection, results indicated that vulnerable children perceived that social health needs ate necessaryJor achieving their opitimal health. Based on the findings, it was recommended that stack holders should pay regular visits to vulnerable children in their homes and in the process show them greater love and care, respect and acceptance. Government should build recreational and vocational centres for them so that vulnerable children would have a sense of belonging with members of the larger society